Defective nano spinel material, preparation method thereof and application of defective nano spinel material in high-temperature inactivation-resistant Rh three-way catalyst
By using defective nanospinel materials as support and combining Rh, a three-effect Rh catalyst with high-temperature resistance to inactivation was formed, which solved the problems of Rh inactivation under high temperature conditions and low-temperature cold start activity, and achieved a significant improvement in the high-temperature stability and low-temperature activity of the catalyst.
Patent Information
- Application Number
- CN202411631556.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
AI Technical Summary
In the existing three-effect catalysts, Rh interacts with the Al2O3 carrier under high temperature conditions, resulting in the formation of RhAlOx species and the sintering of Rh metal particles, resulting in the problems of inactivation and low-temperature cold start activity.
Defective nanospinel material is used as a new support, and MxAl2O4 nanospinel is combined with Rh through the preparation method to form a high-temperature anti-inactivation Rh three-effect catalyst. This method prevents the formation of Rh and Al2O3, inhibits the formation of RhAlOx and the sintering of Rh, thereby improving the high-temperature stability and low-temperature activity of the catalyst.
The high-temperature stability and low-temperature cold-start activity of the Rh three-effect catalyst are significantly improved, the life of the catalyst is extended, the inactivation of Rh is reduced, and the specific surface area and low-temperature performance of the catalyst after high-temperature treatment are maintained.
Smart Images

Figure CN119503858A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a defective nano-spinel material, a preparation method thereof, and application thereof in a high-temperature deactivation-resistant Rh three-way catalyst. Background Art
[0002] With the development of social economy and the continuous expansion of industrial scale, harmful automobile exhaust (CO, NO x , CH compounds) not only seriously threatens human life, health and safety, but also brings huge challenges to ecological and environmental protection. The three-way catalytic converter can efficiently convert harmful automobile exhaust into harmless N2, H2O and CO2, and has now become an essential component of fuel vehicles. Its main component, the three-way catalyst, is composed of precious metal active centers such as Pt, Rh, Pd, an Al2O3 catalyst carrier with a high specific surface area, and rare earth oxide additives such as Ce and La. Among them, Rh has excellent low-temperature NO elimination reaction activity and is an irreplaceable important component. At the same time, Rh will interact with the Al2O3 coating under high temperature conditions to form RhAlO x The deactivation of Rh centers on the Al2O3 surface is a major challenge in the field of three-way catalysis.
[0003] Current research on the deactivation of Rh mainly focuses on modifying the surface of alumina support, depositing organic Ti or organic Zr precursors on the Al2O3 surface to limit the direct contact between Rh and Al2O3, thereby inhibiting the RhAlO x The generation of inactivated species. This method can ensure that the catalyst still maintains good low-temperature cold start activity after hydrothermal aging at 900°C. However, Rh undergoes obvious agglomeration after aging, which is not conducive to reuse. In addition, due to the high price of organic Ti or organic Zr and the cumbersome atomic layer deposition operation, this method is not conducive to practical application.
[0004] Therefore, the development of new nano-carriers to replace Al2O3 can regulate the interaction between Rh and the carrier while achieving the goal of suppressing the RhAlO x Speciation formation and Rh metal particle sintering, which synergistically improve the low-temperature activity and high-temperature stability of the three-way catalyst, are of great significance. Summary of the Invention
[0005] The present invention aims to address the problems of prior art three-way catalysts, such as the generation of RhAlOx at temperatures exceeding 900°C, Rh deactivation, and low activity during cold starts. The present invention provides a defective nanospinel material, its preparation method, and its use in high-temperature, deactivation-resistant Rh three-way catalysts.
[0006] The technical solutions of the present invention are as follows:
[0007] One of the objects of the present invention is to provide a method for preparing defective nanospinel materials, wherein:
[0008] S1: M(NO3)2·nH2O and Al(NO3)3·9H2O are uniformly dispersed in deionized water to obtain a mixed solution;
[0009] S2: adding Na2CO3 solution to the mixed solution obtained in S1 until the molar ratio of (M+Al) to Na2CO3 is 2, stirring evenly, adjusting the pH to 9-11, aging, washing, centrifuging, and drying to obtain a defective nanospinel precursor;
[0010] S3: Take the defective nanospinel precursor of S2 in a porcelain boat, calcine and reduce it in a hydrogen-argon mixture to obtain M x Al2O4 defective nanospinel.
[0011] It is further defined that M of S3 is Fe, Ni, Cu, Zn or Co, and 0.8<x<1.
[0012] It is further defined that the concentration of M(NO3)2·nH2O in the mixed solution of S1 is 0.5-3 mol / L, the concentration of Al(NO3)3·9H2O is 0.5-3 mol / L, and the molar ratio of M(NO3)2·nH2O to Al(NO3)3·9H2O is 1:1.
[0013] It is further defined that the aging time of S2 is 10-35h and the drying temperature is 60-100°C.
[0014] It is further defined that the calcination temperature of S3 is 700-900°C, the volume fraction of the hydrogen-argon mixed gas is 85-95% Ar + 5-15% H2, and the reduction time is 0.5-3h.
[0015] A second object of the present invention is to provide a defective nano-spinel material, which is prepared by the above-mentioned preparation method.
[0016] The third object of the present invention is to provide an application of the above-mentioned defective nano-spinel material in a high-temperature deactivation-resistant Rh three-way catalyst.
[0017] A fourth object of the present invention is to provide a high-temperature deactivation-resistant Rh three-way catalyst, wherein the high-temperature deactivation-resistant Rh three-way catalyst is prepared from the above-mentioned defective nano-spinel material and Rh(NO3)3.
[0018] A fifth object of the present invention is to provide a method for preparing the above-mentioned high-temperature deactivation-resistant Rh three-way catalyst, wherein:
[0019] The defective nano-spinel material is uniformly dispersed in water, Rh(NO3)3 solution is added drop by drop, stirred, evaporated to dryness, and calcined and reduced in a hydrogen-argon mixture to obtain a high-temperature deactivation-resistant Rh three-way catalyst.
[0020] It is further defined that the loading amount of Rh is 1-3 wt%, the stirring time is 1-3 h, and the evaporation temperature is 60-100° C.
[0021] It is further defined that the volume fraction of the hydrogen-argon mixed gas is 85-95% Ar + 5-15% H2, the calcination temperature is 400-600°C, and the reduction time is 2-5h.
[0022] Compared with the prior art, the specific advantages of the present invention are as follows:
[0023] (1) The defective nano-spinel carrier developed by the present invention replaces the traditional Al2O3 carrier, which can eliminate the direct contact between Rh and Al2O3 from the root, and eliminate the RhAlO x It can maintain good sintering resistance without the need for additional doping with Ce or La, and can effectively simplify the complexity of catalyst synthesis. The defective nanospinel prepared by the present invention has a simple synthesis process and can be easily industrialized.
[0024] (2) The defective nanospinel carrier developed in the present invention produces a strong interaction with the loaded Rh, which increases the migration energy barrier of the Rh center and significantly improves the high-temperature stability of the Rh nanoparticles.
[0025] (3) The novel carrier-supported Rh catalyst Rh-M x The specific surface area of Al2O4 before and after high temperature hydrothermal treatment at 900℃ is only 71m 2 / g dropped to 69m 2 / g, with the specific surface area remaining virtually unchanged after high-temperature treatment at 900°C, and the cold-start performance remaining unchanged before and after aging at 900°C for 4 hours. This significantly inhibits Rh deactivation, greatly extending the catalyst lifespan and reducing the cost increase caused by expensive Rh deactivation. The T50 (the temperature at which the conversion rate reaches 50%; the lower the temperature, the better the catalyst performance) for the three pollutants CO, NO, and C3H6 is approximately 150°C, demonstrating that the present invention combines excellent low-temperature cold-start activity with high-temperature sintering resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the XRD diffraction spectrum of the defective nanospinel precursor ZnAl-LDH of Example 1;
[0027] Figure 2 is Zn in Example 1 x Al2O4 and 1% Rh / Zn x XRD diffraction pattern of Al2O4;
[0028] Figure 3 1% Rh / Zn of Example 1 x Transmission electron microscope image of Al2O4;
[0029] Figure 4 This is a comparison chart of the NO elimination performance of Example 1, Comparative Example 1 and Comparative Example 2 before and after aging at 900°C for 4 hours;
[0030] Figure 5 This is a comparison chart of the CO elimination performance of Example 1, Comparative Example 1, and Comparative Example 2 before and after aging at 900°C for 4 hours;
[0031] Figure 6 This is a comparison chart of the C3H6 elimination performance of Example 1, Comparative Example 1 and Comparative Example 2 before and after aging at 900°C for 4 hours. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0033] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods, and instruments used are conventional in the art and can be obtained commercially by those skilled in the art unless otherwise specified.
[0034] As used in the following examples, the terms "comprising," "including," "having," "containing," or any other variations thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0035] When amount, concentration or other value or parameter are represented with the range of scope, preferred range or a series of upper preferred value and lower preferred value limit, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, and no matter whether this scope is disclosed separately.For example, when disclosing scope "1 to 5", described scope should be interpreted as including scope "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc.When numerical range is described in this article, unless otherwise stated, otherwise this scope is intended to include its end value and all integers and fractions within the scope.In this application specification and claims, range limitation can be combined and / or interchanged, and if these ranges are not otherwise stated, include all subranges contained therein.
[0036] The indefinite articles "a" and "an" before the elements or components of the present invention do not limit the quantity requirement (i.e. the number of times they appear). Therefore, "a" or "an" should be interpreted as including one or at least one, and elements or components in the singular also include plural forms, unless the quantity clearly refers to only the singular form.
[0037] The term "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it necessarily refer to a separate or selective embodiment that is mutually exclusive of other embodiments.
[0038] The endpoints of the ranges and any values disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.
[0039] Example 1:
[0040] Preparation of ZnAl2O4 defective nanospinel:
[0041] S1: 14 mmol Zn(NO3)2·6H2O and 14 mmol Al(NO3)3·9H2O were uniformly dispersed in 28 mL deionized water to obtain a mixed solution;
[0042] S2: 28 mL of 0.5 mol / L Na2CO3 solution was added to the mixed solution obtained in S1, and after stirring evenly, NaOH (4 mol / L) solution was added dropwise to pH = 10. The mixture was allowed to stand at room temperature for 16 h, washed three times, centrifuged at 3500 rpm three times, and dried at 100°C for 12 h to obtain a defective nanospinel precursor (ZnAl-LDH);
[0043] S3: Take the ZnAl-LDH of S2 in a porcelain boat, and heat it to 900℃ at a heating rate of 5℃ / min under the condition of a mixed gas volume of 90% Ar+10% H2, and calcine it for 2h to obtain ZnAl2O4 defect nanospinel.
[0044] Preparation of 1% Rh-ZnAl2O4:
[0045] Take 1g ZnAl2O4 and disperse it evenly in 50mL water, add 0.1mL of 1mol / L Rh(NO3)3 solution, stir for 3h, evaporate and soak at 80℃, and heat at a rate of 5℃ / min to 400℃ under the conditions of mixed gas volume of 90% Ar+10% H2 and flow rate of 50mL / min, and reduce and calcine for 2h to obtain 1% Rh / ZnAl2O4.
[0046] Example 2:
[0047] Preparation of CuAl2O4 defective nanospinel:
[0048] S1: 14 mmol Cu(NO3)2·6H2O and 14 mmol Al(NO3)3·9H2O were uniformly dispersed in 28 mL deionized water to obtain a mixed solution;
[0049] S2: 28 mL of 0.5 mol / L Na2CO3 solution was added to the mixed solution obtained in S1, and after stirring, NaOH (4 mol / L) solution was added dropwise until the pH was 10. The mixture was aged for 16 h, washed 3 times, centrifuged at 3500 rpm 3 times, and dried at 100°C for 12 h to obtain a defective nanospinel precursor (CuAl-LDH).
[0050] S3: Take the CuAl-LDH of S2 in a porcelain boat, and heat it to 900°C at a heating rate of 5°C / min in a mixed gas volume of 90% Ar + 10% H2, and calcine it for 2h to obtain CuAl2O4 defect nanospinel.
[0051] Preparation of 1% Rh-CuAl2O4:
[0052] Take 1gCuAl2O4 and disperse it evenly in 50mL water, add 0.1mL of 1mol / L Rh(NO3)3 solution, stir for 3h, evaporate and soak at 80℃, and heat at a rate of 5℃ / min to 400℃ under the conditions of mixed gas volume of 90% Ar+10% H2 and flow rate of 50mL / min, and reduce and calcine for 2h to obtain 1%Rh / CuAl2O4.
[0053] Example 3:
[0054] Preparation of CoAl2O4 defective nanospinel:
[0055] S1: 14 mmol Co(NO3)2·6H2O and 14 mmol Al(NO3)3·9H2O were uniformly dispersed in 28 mL deionized water to obtain a mixed solution;
[0056] S2: 28 mL of 0.5 mol / L Na2CO3 solution was added to the mixed solution obtained in S1, and after stirring evenly, NaOH (4 mol / L) solution was added dropwise until the pH was 10. The mixture was aged for 16 h, washed 3 times, centrifuged at 3500 rpm 3 times, and dried at 100°C for 12 h to obtain a defective nanospinel precursor (CoAl-LDH).
[0057] S3: Take the CoAl-LDH of S2 in a porcelain boat, and heat it to 900°C at a heating rate of 5°C / min in a mixed gas volume of 90% Ar + 10% H2, and calcine it for 2h to obtain CoAl2O4 defect nanospinel.
[0058] Preparation of 1% Rh-CoAl2O4:
[0059] Take 1g CoAl2O4 and disperse it evenly in 50mL water, add 0.1mL of 1mol / L Rh(NO3)3 solution, stir for 3h, evaporate and soak at 80℃, and heat at a rate of 5℃ / min to 400℃ under the conditions of a mixed gas volume of 90% Ar+10% H2 and a flow rate of 50mL / min. Reduce and calcine for 2h to obtain 1% Rh / CoAl2O4.
[0060] Example 4:
[0061] Preparation of FeAl2O4 defective nanospinel:
[0062] S1: 14 mmol Fe(NO3)2·6H2O and 14 mmol Al(NO3)3·9H2O were uniformly dispersed in 28 mL deionized water to obtain a mixed solution;
[0063] S2: 28 mL of 0.5 mol / L Na2CO3 solution was added to the mixed solution obtained in S1, and after stirring, NaOH (4 mol / L) solution was added dropwise until the pH was 10. The mixture was aged for 16 h, washed 3 times, centrifuged at 3500 rpm 3 times, and dried at 100°C for 12 h to obtain a defective nanospinel precursor (FeAl-LDH).
[0064] S3: Take the FeAl-LDH of S2 in a porcelain boat, and heat it to 900℃ at a heating rate of 5℃ / min under the condition of a mixed gas volume of 90% Ar+10% H2, and calcine it for 2h to obtain FeAl2O4 defect nanospinel.
[0065] Preparation of 1% Rh-FeAl2O4:
[0066] Take 1g FeAl2O4 and disperse it evenly in 50mL water, add 0.1mL of 1mol / L Rh(NO3)3 solution, stir for 3h, evaporate and soak at 80℃, and heat at a rate of 5℃ / min to 400℃ under the conditions of mixed gas volume of 90% Ar+10% H2 and flow rate of 50mL / min, and reduce and calcine for 2h to obtain 1% Rh / FeAl2O4.
[0067] Example 5:
[0068] Preparation of NiAl2O4 defective nanospinel:
[0069] S1: 14 mmol Ni(NO3)2·6H2O and 14 mmol Al(NO3)3·9H2O were uniformly dispersed in 28 mL deionized water to obtain a mixed solution;
[0070] S2: 28 mL of 0.5 mol / L Na2CO3 solution was added to the mixed solution obtained in S1, and after stirring, NaOH (4 mol / L) solution was added dropwise until the pH was 10. The mixture was aged for 16 h, washed 3 times, centrifuged at 3500 rpm 3 times, and dried at 100°C for 12 h to obtain a defective nanospinel precursor (NiAl-LDH).
[0071] S3: Take the NiAl-LDH of S2 in a porcelain boat, and heat it to 900°C at a heating rate of 5°C / min under the condition of a mixed gas volume of 90% Ar + 10% H2, and calcine it for 2h to obtain NiAl2O4 defect nanospinel.
[0072] Preparation of 1% Rh-NiAl2O4:
[0073] Take 1g NiAl2O4 and disperse it evenly in 50mL water, add 0.1mL of 1mol / L Rh(NO3)3 solution, stir for 3h, evaporate and soak at 80℃, and heat at a rate of 5℃ / min to 400℃ under the conditions of mixed gas volume of 90% Ar+10% H2 and flow rate of 50mL / min, and reduce and calcine for 2h to obtain 1% Rh / NiAl2O4.
[0074] Comparative Example 1:
[0075] Preparation of 1% Rh / Al2O3:
[0076] Take 1gAl2O3 and disperse it evenly in 50mL water, add 0.1mL of 1mol / L Rh(NO3)3 solution, stir for 3h, evaporate and soak at 80℃, and heat at a rate of 5℃ / min to 400℃ under the conditions of mixed gas volume of 90% Ar+10% H2 and flow rate of 50mL / min, and reduce and calcine for 2h to obtain 1%Rh / Al2O3.
[0077] Comparative Example 2:
[0078] Preparation of 30% ZnAl2O4-Al2O3:
[0079] Take 3.1337g Zn(NO3)2.6H2O and fully dissolve it in 2.8ml deionized water, add 2.0003g Al2O3, stir evenly, let it stand for 8h, then dry it at 120℃ for 12h, and finally calcine it at 900℃ for 4h to obtain a 30% ZnAl2O4-Al2O3 composite support.
[0080] Preparation of 1% Rh / 30% ZnAl2O4-Al2O3:
[0081] Take 1g ZnAl2O4-Al2O3 and disperse it evenly in 50mL water, add 0.1mL of 1mol / L Rh(NO3)3 solution, stir for 3h, evaporate and soak at 80℃, and heat at a rate of 5℃ / min to 400℃ under the conditions of mixed gas volume of 90% Ar+10% H2 and flow rate of 50mL / min, and reduce and calcine for 2h to obtain 1% Rh / ZnAl2O4-Al2O3.
[0082] 900℃ hydrothermal aging test:
[0083] 60 mg of the catalyst to be tested was placed in a quartz tube, which was then placed in a fixed-bed reactor. Under the conditions of a gas flow rate of 200 mL / min, a CO concentration of 20,000 ppm, a NO concentration of 500 ppm, a propylene concentration of 2,110 ppm, an O2 concentration of 19,250 ppm, and Ar balance, the temperature was raised to 900°C at a heating rate of 10°C / min and aged for 4 h. The changes in the specific surface area of the catalyst before and after aging are shown in Table 1.
[0084] Table 1: Changes in specific surface area of catalysts before and after 900℃ hydrothermal aging test
[0085] sample <![CDATA[Specific surface area before test (m 2 / g)]]> <![CDATA[Specific surface area after test (m 2 / g)]]> Example 1 71 67
[0086] As shown in Table 1, the specific surface area of the high-temperature deactivation-resistant Rh three-way catalyst prepared by the present invention hardly changes after high-temperature treatment at 900°C, proving that Rh does not agglomerate under high-temperature conditions.
[0087] Figure 1 It shows that Zn in Example 1 x Successful synthesis of Al2O4-defective nanospinel precursor ZnAl-LDH.
[0088] Figure 2 It shows that Zn in Example 1 x Al2O4 defect nanospinel precursor and 1% Rh-Zn x Al2O4 three-way catalyst was successfully synthesized.
[0089] Figure 3 The 1% Rh-Zn in Example 1 is shown x Zn Al2O4 three-way catalyst x The particle size of Al2O4 is about 50nm, and Rh is loaded on the carrier in the form of nanoparticles.
[0090] Figure 4 The 1% Rh-Zn in Example 1 is shown x The NO complete elimination performance of Al2O4 remains basically unchanged before and after aging at 900℃. The NO complete elimination performance of 1% Rh-Al2O3 in Comparative Example 1 decreases by about 100℃ after aging at 900℃. The NO complete elimination performance of 1% Rh-ZnAl2O4-Al2O3 in Comparative Example 2 decreases by about 50℃.
[0091] Figure 5 The 1% Rh-Zn in Example 1 is shown x The CO complete elimination performance of Al2O4 remains basically unchanged before and after aging at 900℃. The CO complete elimination performance of 1% Rh-Al2O3 in Comparative Example 1 decreases by about 100℃ after aging at 900℃. The CO complete elimination performance of 1% Rh-ZnAl2O4-Al2O3 in Comparative Example 2 decreases by about 50℃.
[0092] Figure 6 The 1% Rh-Zn in Example 1 is shown x The complete elimination performance of C3H6 of Al2O4 remains basically unchanged before and after aging at 900℃. The complete elimination performance of C3H6 of 1% Rh-Al2O3 in comparative example 1 decreases by about 100℃ after aging at 900℃. The complete elimination performance of C3H6 of 1% Rh-ZnAl2O4-Al2O3 in comparative example 2 decreases by about 50℃.
[0093] Figure 4 、 Figure 5 and Figure 6 The results show that the high-temperature deactivation-resistant Rh three-way catalyst prepared by the present invention has basically unchanged performance in completely eliminating NO, CO and C3H6 under aging at 900°C, proving that the high-temperature deactivation-resistant Rh three-way catalyst prepared by the present invention overcomes the problem of Rh deactivation at 900°C. Under these conditions, the T50 (the temperature at which the conversion rate reaches 50%; the lower the temperature, the better the catalyst performance) of the three pollutants CO, NO and C3H6 is approximately 150°C, proving that the present invention solves the problem of low cold start activity at low temperatures.
[0094] The foregoing are merely preferred embodiments of the present invention. These embodiments are all different implementations based on the overall concept of the present invention. The scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A method for preparing defective nano-spinel material, characterized in that: The method: S1: M(NO3)2·nH2O and Al(NO3)3·9H2O are uniformly dispersed in deionized water to obtain a mixed solution; S2: Add Na2CO3 solution to the mixed solution obtained in S1 until the molar ratio of (M+Al) to Na2CO3 is 2, stir evenly, adjust the pH to 9-11, age, wash, centrifuge, and dry to obtain a defective nanospinel precursor; S3: Take the defective nanospinel precursor of S2 in a porcelain boat, calcine and reduce it in a hydrogen-argon mixture to obtain M x Al2O4 defective nanospinel.
2. The method according to claim 1, characterized in that M of S3 is Fe, Ni, Cu, Zn or Co, and 0.8<x<1.
3. The method according to claim 1, characterized in that In the mixed solution of S1, the concentration of M(NO3)2·nH2O is 0.5-3 mol / L, the concentration of Al(NO3)3·9H2O is 0.5-3 mol / L, and the molar ratio of M(NO3)2·nH2O to Al(NO3)3·9H2O is 1:
1.
4. The method according to claim 1, characterized in that: The aging time of S2 is 10-35h, and the drying temperature is 60-100°C; the calcination temperature of S3 is 700-900°C, the volume fraction of the hydrogen-argon mixed gas is 85-95% Ar+5-15% H2, and the reduction time is 0.5-3h.
5. A defective nanospinel material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the defective nano-spinel material according to claim 5 in a high temperature deactivation-resistant Rh three-way catalyst.
7. A high temperature deactivation resistant Rh three-way catalyst, characterized in that: It is prepared from the defective nano-spinel material as claimed in claim 5 and Rh(NO3)3.
8. The method for preparing the high temperature deactivation resistant Rh three-way catalyst according to claim 7, characterized in that: The method: The defective nano-spinel material described in claim 5 is uniformly dispersed in water, Rh(NO3)3 solution is added drop by drop, stirred, evaporated to dryness, and calcined and reduced in a hydrogen-argon mixed gas to obtain a high-temperature deactivation-resistant Rh three-way catalyst.
9. The method according to claim 8, characterized in that The loading amount of Rh is 1-3wt%, the stirring time is 1-3h, and the evaporation temperature is 60-100°C.
10. The method according to claim 8, characterized in that The volume fraction of the hydrogen-argon mixed gas is 85-95% Ar+5-15% H2, the calcination temperature is 400-600°C, and the reduction time is 2-5h.